INTRODUCTION - Serafimovski, Todor (Geologica Macedonica, 2015)
The Geologica Macedonica is an official publication ofthe "Goce Delčev" University, Faculty of Natural and TechnicalSciences, Štip, Republic of Macedonia. It is published twiceyearly. The journal publishes original scientific papers, shortcommunications, reviews, professional and educationalpapers from all fields of Mining, Geology, Petrology, Mineralogyand Geochemistry....